Web-Based Panoramic VR for a Resort - Sofeer, Hayiyusuf (2003)
This study is to develop a web site incorporating a panoramic virtual reality (VR), sometimes called virtual environments (VE), for a hotel and this technology can create a unique environment where the customer can stay anywhere in the world and explore via World Wide Web. This approach uses a web-based panoramic VR as a tool to a create a website for application in a real project. This project involves the development of a website as an aid to promote a new hotel in Pattani, Thailand, the C.S. Pattani Hotel (http://www.cspattani.com). This paper explores the practical and technical procedures such as photo capture, digital stitch, panoramic output and preview movie in the development of the panoramic model.